Penyuluhan Peluang Bisnis Berwirausaha Di Masa New Normal - Febi Nur Biduri; Eka Yuniar Ernawati; Widiastuti; Yessy Harun (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
Abstract The most effective and inexpensive media promotion to trade our  products during the New Normal era is in the digital network, because people are currently still hesitant to leave the house. Entrepreneurship that has emerged on the surface today are culinary, services, and content creators. So that business competition in the network is increasingly visible and there are many business people who promote their merchandise through the internet network. Due to the problems mentioned above, we carry out our counseling on business and entrepreneurship opportunities with the target of providing suitable entrepreneurial alternatives  in the New Normal era for the Indonesian people and the teachers of Madrasah Ibtidaiyah Tarbiyatul Islamiyah, as giving a counseling program which is carried out in a network using zoom media,  the presentation of  entrepreneurship theory from entrepreneurship lecturer at Darma Persada University and the testimony about entrepreneurship by a lecturer at Darma Persada University who has culinary business. The results of these counseling activities to the teachers and the employees of Madrasah Ibtidaiyah Tarbiyatul Islamiyah would hopefully be able to open their knowledge about the new ideas and creativities in entrepreneurship  to determine the suitable type of entrepreneurship in accordance with the environment around Nobotengah village. Besides, we hope through this counseling there will be the new adaptable enterpreneurships which create their products uniquely  in the New Normal era. AbstrakPromosi dagang  yang paling efektif serta murah dimasa New Normal adalah dalam jaringan, dikarenakan masyarakat saat ini masih ragu untuk keluar rumah, Kewirausahaan yang banyak muncul kepermukaan dimasa ini adalah kuliner, jasa, dan pembuat konten di media social.Sehingga persaingan bisnis dalam jaringan semakin terlihat dan banyak pelaku bisnis yang memasarkan barang dagang mereka melalui jaringan internet. Dikarenakan permasalahan yang disebutkan diatas maka kami melaksanakan penyuluhan peluang bisnis dan berwirausaha ini dengan target untuk memberikan alternatif kewirausahaan yang sesuai di masa New Normal bagi Masyarakat Indonesia dan guru-guru Madrasah Ibtidaiyah Tarbiyatul. Penyuluhan dilaksanakan 1 kali, penyuluhan dilakukan dalam jaringan menggunakan media zoom, penyuluhan berupa pemaparan teori kewirausahaan oleh Dosen Kewirausahaan Universitas Darma Persada dan juga testimoni mengenai kewirausahaan oleh seorang Dosen Universitas Darma Persada yang memiliki usaha dibidang kuliner. Hasil kegiatan penyuluhan yang di berikan kepada para guru dan karyawan Madrasah Ibtidaiyah Tarbiyatul Islamiyah adalah munculnya wawasan dalam hal berwirausaha, munculnya ide baru dan kreativitas dalam menentukan jenis kewirausahaan sesuai dengan lingkungan sekitar dusun Nobotengah. Para calon wirausahawaan juga mempunyai kemampuan adaptasi produk sesuai dengan kondisi new era.